PENGARUH KEPRIBADIAN DAN KETELADANAN GURU KRISTEN TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK DI SMK NEGERI TOMPASO BARU, DITINJAU SECARA TEOLOGIS BERDASARKAN I TIMOTIUS 4:12 - Kewas, Jendry (STT INDONESIA MANADO, 2020)
Education has an important role to produce quality human resources both in terms of intellectual and spiritual. This is in accordance with the Law of the Republic of Indonesia No. 20 of 2003 concerning National Education System Article 3 which states that